Michael Clarke and Ron Hague (eds.), European Defence Cooperation: America, Britain and NATO, Fulbright Papers 7, Manchester: Manchester University Press, 1990, 177 s., £ 35.00. - Heurlin, Bertel (Politica, 1990)
-